Financial Statement Profit and Loss of H.Amid Shop - Aini, Qurrotu (Operations Research: International Conference Series, 2021)
Financial statements are one of the important sources of information and media used by business managers in the decision-making process to find out information regarding financial position. One type of financial report is an income statement or income and expense report. In small shops in the village, one of which is Toko H.Amid, the bookkeeping has not followed the proper reporting rules. Therefore, the purpose of writing this paper is to provide an overview of the correct financial reporting rules and to find out whether the H.Amid Store has run its store properly by looking at the H.Amid Store’s ability to collect net profit. The method used to compile the H.Amid Store’s profit and loss financial statements is to conduct interviews with the H.Amid Store owners regarding income, expenses, and others. Then the data is calculated and then compiled into the income statement. To determine the ability of H.Amid Stores in collecting net profit, one of the profitability ratio analysis is used, namely Net Profit Margin (NPM). Based on the results of the preparation of the profit and loss financial statements at the H.Amid Store, the net profit for the 2020 period was IDR 98,461,667,- and net profit in 2021 is IDR 157,956,667. Then from the results of profitability analysts, the Net Profit Margin which increased from 0.69% in 2020 to 1.07% in 2021 and was obtained in 2020 to 2021 close to number 1, indicating that this company is healthy because the bigger the ratio, the better because it is considered the company’s ability to earn profit is quite high.